Research progress of drug-related adverse reactions in hepatitis C patients and related nursing interventions (丙肝患者药物相关性不良反应及护理干预的研究进展) - ZHANG Xiaoning (张晓宁); WANG Xinhua (王新华); CHEN Ying (陈英) (中西医结合护理)
Combination of peginterferon-alpha (PEG-IFN) and ribavirin (RBV) therapy is the current standard of care for chronic hepatitis C. This paper reviewed the studies of drug-related adverse reactions in hepatitis C patients who received PEG-IFN and RBV therapy, in order to increase awareness of medical staff and patients on drug-related adverse reactions, and provide reference for implementation of comprehensive interventions. (聚乙二醇干扰素(PEG－IFN)联合利巴韦林(RBV)的方案和直接抗病毒药物(DAA)是目前临床较为常见丙型病毒性肝炎治疗方案。本文对两种治疗方案的不良反应及护理干预进行综述, 旨在引起医护人员和患者对不良反应的关注及再认识, 为医护人员提供全维度的护理干预措施提供参考。)